Immune Checkpoint Inhibitors in Breast Cancer - Haruto, Yuminaga (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The incidence of breast cancer has risen dramatically over the past few decades and has become the most common malignancy in women. By 2040, it is expected that there will be more than 3 million new cases of breast cancer and more than 1 million deaths per year. The incidence of breast cancer has risen dramatically over the past few decades and has become the most common malignancy in women. By 2040, it is expected that there will be more than 3 million new cases of breast cancer and more than 1 million deaths per year. Immune checkpoint therapeutics was significant technological breakthrough on cancer treatment programs. It uses the body’s immune system targets and eliminates cancer cells. This therapy maintains self-tolerance and modulates the immune response to minimize tissue damage during infection. This therapy inhibits immune checkpoints such as PD-1, PD-L1, and CTLA-4, which tumors exploit to evade immune detection. By blocking these pathways, immune checkpoint inhibitors can reactivate T cells, enabling them to recognize and attack breast cancer cells. This essay will explain how does checking for inhibitors help T cells recognize the breast tumor cells, and some drugs specialize in PD-1 and CTLA-4.